2021
DOI: 10.1097/md.0000000000024551
|View full text |Cite
|
Sign up to set email alerts
|

Warm acupuncture therapy for Primary sciatica

Abstract: Introduction: This meta-analysis aims to assess the effectiveness and safety of warm acupuncture therapy for treating Primary sciatica. Methods: The following 9 databases will be search from their inception to December 6, 2020: MEDLINE, EMBASE, the Cochrane Central Register of Controlled Trials (CENTRAL), the Chinese Biomedical Literature Database (CBM), the Chinese Medical Current Content (CMCC), the Wan-Fang Database and the China National Knowledge I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…The results of clinical studies on acupuncture therapy for sciatica showed that acupuncture is effective in relieving its symptoms (Liu et al, 2019 ; Yu et al, 2022 ). The effects of acupuncture treatment are also determined by selecting the appropriate acupuncture method, including manual acupuncture (MA) with twirling, lifting, and thrusting manipulation, electroacupuncture (EA) with an electric microcurrent device, and warm acupuncture (WA) with a combination of acupuncture and moxibustion treatment (Cao et al, 2021 ). According to the efficacy and safety of acupuncture for pain relief, patients with sciatica often give consent to undergo acupuncture treatment in China.…”
Section: Introductionmentioning
confidence: 99%
“…The results of clinical studies on acupuncture therapy for sciatica showed that acupuncture is effective in relieving its symptoms (Liu et al, 2019 ; Yu et al, 2022 ). The effects of acupuncture treatment are also determined by selecting the appropriate acupuncture method, including manual acupuncture (MA) with twirling, lifting, and thrusting manipulation, electroacupuncture (EA) with an electric microcurrent device, and warm acupuncture (WA) with a combination of acupuncture and moxibustion treatment (Cao et al, 2021 ). According to the efficacy and safety of acupuncture for pain relief, patients with sciatica often give consent to undergo acupuncture treatment in China.…”
Section: Introductionmentioning
confidence: 99%
“…It is assumed that the steady and deep heat transfer introduced by the inserted needles will exert an effective anti-inflammatory effect at the local lesion, resulting in a strong analgesic effect. [8][9][10] There are more and more clinical studies on the efficacy of warm acupuncture in treating sciatica, but the systematic review of the efficacy of warm acupuncture is still lacking. The objective of this study was to evaluate the efficacy and safety of warm acupuncture combined with conventional Western medicine in the treatment of sciatica.…”
Section: Introductionmentioning
confidence: 99%
“…It is assumed that the steady and deep heat transfer introduced by the inserted needles will exert an effective anti-inflammatory effect at the local lesion, resulting in a strong analgesic effect. [8–10]…”
Section: Introductionmentioning
confidence: 99%